SURGICAL OUTCOME OF INTRADURAL SPINAL TUMOURS - Ali, Gohar; Khan, Shahbaz Ali; Afridi, Ehtisham Ahmed Khan; Aurangzeb, Ahsan; Ali, Asghar; Khalid, Shah (Journal of Ayub Medical College Abbottabad, 2020)
Background: This study was conducted to determine the short-term outcome of surgical procedure in patients having spinal intradural tumours. Methods: This cross-sectional study was conducted from 26 April 2016 to 25 March 2019 on 56 patients after approval from hospitals ethical and research committee. MRI spine were studied in detail for all patients to know about the site, size, shape, extent and nature of the tumour. History, examination, pre-operative MRI findings, post-operative findings were documented in patient's pro forma. Short term as well as long term post-operative results were documented after surgery, during stay at hospital and follow-up visits till 6 months. Results: In this study, 56 patients with spinal intradural tumours were observed. Male to female ratio was 1.33:1. Age ranged from 5-65 years (32.5±14.6). Paraparesis, hypesthesia, sphincter dysfunction were the presenting symptoms in most of the patients. 47% (21) patients improved according to MRC Grading system 46% (20) patients remained static 7% (3) patients deteriorated. Wound infection was found in 7 (12.5%) patients, followed by Neurological Deficit in 5 (8.9%) cases, Meningitis was found in 2 (3.57%), CSF leak was noted in 4 (7.14%) patients and mortality in 1 (1.7%) of the case. Conclusion: Surgery of the intradural spinal tumours carry good neurological outcome with acceptable complication rates. Keywords: Spinal intradural tumours; Neurological deficit; Wound infection; Meningitis; CSF leak